Surface-Displayed Amuc_1100 From Akkermansia muciniphila on Lactococcus lactis ZHY1 Improves Hepatic Steatosis and Intestinal Health in High-Fat-Fed Zebrafish - Zhang, Feng-Li; Yang, Ya-Lin; Zhang, Zhen; Yao, Yuan-Yuan; Xia, Rui; Gao, Chen-Chen; Du, Dong-Dong; Hu, Juan; Ran, Chao; Liu, Zhen; Zhou, Zhi-Gang (Frontiers in Nutrition, 2021)
Fatty liver and intestinal barrier damage were widespread in most farmed fish, which severely restrict the development of aquaculture. Therefore, there was an urgent need to develop green feed additives to maintain host liver and intestinal health. In this study, a probiotic pili-like protein, Amuc_1100 (AM protein), was anchored to the surface of Lactococcus lactis ZHY1, and the effects of the recombinant bacteria AM-ZHY1 on liver fat accumulation and intestinal health were evaluated. Zebrafish were fed a basal diet, high-fat diet, and high-fat diet with AM-ZHY1 (108 cfu/g) or control bacteria ZHY1 for 4 weeks. Treatment with AM-ZHY1 significantly reduced hepatic steatosis in zebrafish. Quantitative PCR (qPCR) detection showed that the expression of the lipogenesis [peroxisome-proliferator-activated receptors (PPARγ), sterol regulatory element-binding proteins-1c (SREBP-1c), fatty acid synthase (FAS), and acetyl-CoA carboxylase 1 (ACC1)] and lipid transport genes (CD36 and FABP6) in the liver were significantly downregulated (p < 0.05), indicating that AM-ZHY1 could reduce liver fat accumulation by inhibiting lipid synthesis and absorption. Moreover, supplementing AM-ZHY1 to a high-fat diet could significantly reduce serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels, indicating that liver injury caused by high-fat diets was improved. The expression of tumor necrosis factor (TNF)-a and interleukin (IL)-6 in the liver decreased significantly (p < 0.05), while IL-1β and IL-10 did not change significantly in the AM-ZHY1 group. Compared to the high-fat diet-fed group, the AM-ZHY1 group, but not the ZHY1 group, significantly increased the expression of intestinal tight junction (TJ) proteins (TJP1a, claudina, claudin7, claudin7b, claudin11a, claudin12, and claudin15a; p < 0.05). Compared to the high-fat diet group, the Proteobacteria and Fusobacteria were significantly reduced and increased in the AM-ZHY1 group, respectively. In conclusion, the recombinant bacteria AM-ZHY1 has the capacity to maintain intestinal health by protecting intestinal integrity and improving intestinal flora structure and improving fatty liver disease by inhibiting lipid synthesis and absorption. This study will lay a foundation for the application of AM protein in improving abnormal fat deposition and restoring the intestinal barrier in fish.